2020
DOI: 10.1007/s12551-020-00702-8
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Reviews—Quantitative analysis of biological phenomenon

Abstract: This Editorial first describes the articles constituting the current Issue (Volume 12 Issue 3). It then goes on to outline the formal invitation procedure for those interested in submitting a review article to the journal. The Editorial concludes by describing the nomination process for the 2021 Michèle Auger Award for Young Scientists' Independent Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Directly after this Editorial (Hall 2021) is the latest instalment of the Biophysical Reviews' 'Meet the Editors Series' (Vassalli 2021). In beginning, this biographical endeavor the journal placed its focus on the five Executive Editors (Olson 2020; Nagayama 2020; Itri 2020; Ho 2020; Jagannathan 2020).…”
Section: Description Of Issue Contentsmentioning
confidence: 99%
“…Directly after this Editorial (Hall 2021) is the latest instalment of the Biophysical Reviews' 'Meet the Editors Series' (Vassalli 2021). In beginning, this biographical endeavor the journal placed its focus on the five Executive Editors (Olson 2020; Nagayama 2020; Itri 2020; Ho 2020; Jagannathan 2020).…”
Section: Description Of Issue Contentsmentioning
confidence: 99%
“…Nominations can be made via email in the form described above to any of the following. For those interested in entering (or nominating another) additional details about the judging and selection of winners for the previous years' competitions can be found in the following references: Hall (2020bHall ( , 2020cHall ( , 2020d; Hall (2021bHall ( , 2021c. The 2020 winner's published review article can be found here (Zidovska 2020) with the 2021 winner's published review article set to appear in the upcoming Issue 4.…”
Section: A Well-written Commentarymentioning
confidence: 99%
“…Volume 12 Issue 3 (Hall 2020d ) was a regular Issue that contained eleven articles. With no set theme, the contributed articles covered a range of topics with some of the highlight review pieces dealing with Brillouin microscopy (Antonacci et al 2020 ); cellular imaging using atomic force microscopy (Zapotoczny et al 2020 ); and exploration of novel second messenger systems (Petchiappan et al 2020 ) and laboratory based studies of evolution (Horinouchi and Furusawa 2020 ).…”
Section: Highlights Of 2020mentioning
confidence: 99%